Pendampingan Pelaporan Pajak Badan - Leny Suzan; Dewa Putra Krishna Mahardika; Koenta Adji (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Business tax reporting for company is a requirement that must be fulfilled every year. For small and micro entrepreneurs who have limited human resources who understand taxation, the obligation to report taxes can be an important issue that can lead to errors in reporting and paying taxes. With this background, the community service team from the Faculty of Economics and Business, Telkom University, carried out community service activities with the theme "Assistance in Corporate Tax Reporting" aimed at business actors who are members of the Indonesian Consultants Association (Perkindo) in the West Java region. The activity was held on February 29 2024 with a total of 25 participants. The aim of carrying out community service activities this time is to increase the awareness of business actors regarding the tax regulations currently in force as well as improve the skills of business actors in the issue of calculating and reporting taxes.